2008
DOI: 10.1021/ef8006245
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Novozym 435 and Amberlyst 15 as Heterogeneous Catalyst for Production of Biodiesel from Palm Fatty Acid Distillate

Abstract: Palm fatty acid distillate (PFAD), a byproduct from the palm oil refinery process, has recently been utilized as an alternative feedstock for biodiesel (BD) production via homogeneous acid-catalyzed esterification. This process suffers from catalyst recovery, wastewater treatment, and BD purification. To minimize the problem, heterogeneous catalysts, Novozym 435 (immobilized Candida antarctica lipase B) and Amberlyst 15 (acidic styrene-divinylbenzene sulfonated ion-exchange resin), are tested and their catalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(44 citation statements)
references
References 14 publications
4
38
0
2
Order By: Relevance
“…As a result alternative raw materials have been investigated and these include non-edible oils such as Jatropha Curacas [8], by-products from oil refining such as palm fatty acid distillate [9], animal fats, algal oil [10] and used cooking oil (UCO) [5,11]. UCO is a waste material and this means that it is possible to reduce the amount of waste going to landfill and use a relatively cheap material.…”
Section: Fig 1 Schematic Representation Of the Transesterification mentioning
confidence: 99%
See 3 more Smart Citations
“…As a result alternative raw materials have been investigated and these include non-edible oils such as Jatropha Curacas [8], by-products from oil refining such as palm fatty acid distillate [9], animal fats, algal oil [10] and used cooking oil (UCO) [5,11]. UCO is a waste material and this means that it is possible to reduce the amount of waste going to landfill and use a relatively cheap material.…”
Section: Fig 1 Schematic Representation Of the Transesterification mentioning
confidence: 99%
“…It has been shown that Novozyme 435 can be used to catalyse transesterification and hydrolysis reactions for the production of biodiesel however the fastest reaction rates are achieved when Novozyme 435 is used to esterify free fatty acids [24]. The work to date has focused on the esterification of material with a high concentration of free fatty acids such as palm fatty acid distillate which contains more than 93 wt% FFAs [9] and soybean oil deodorizer distillate containing 80 wt% FFAs [25]. To date the use of Novozyme 435 to convert the FFAs in UCO to biodiesel prior to transesterification has not been reported.…”
Section: Fig 1 Schematic Representation Of the Transesterification mentioning
confidence: 99%
See 2 more Smart Citations
“…However, waste cooking oils contain a high amount of free fatty acids, which is a problem for biodiesel production by the traditional process (homogeneous alkali-catalyzed transesterification) [8,9]. Different solid acids such as resins with sulfonic acid groups [10][11][12][13][14], zeolites [15][16][17], solid super acid catalysts [18] and carbonaceous catalysts [19] have been used as catalysts in the conversion of waste cooking oil containing a high amount of free fatty acids into biodiesel.…”
Section: Introductionmentioning
confidence: 99%